HE USE OF SINO-VIETNAMESE VOCABULARY IN TRANSLATION OF BUSINESS ENGLISH BY FOURTH-YEAR STUDENTS OF TRANSLATION AND INTERPRETING DIVISION, FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION - Trần, Hà Thu (2020)
This study reflected the reality of taking advantage of the Sino-Vietnamese vocabulary in translation of business-related documents by the fourth-year students in Translator and Interpreting Division, Faculty of English Language Teacher Education, University of Foreign Languages and International Studies. In addition, the study was conducted to identify translation strategies and procedures applied to translate economic terminology from English into Vietnamese using SinoVietnamese vocabulary. To achieve these aims, the data were collected by questionnaire. Overall, the exploitation of Sino-Vietnamese vocabulary in translation of business-related documents has not been paid proper attention by the students. This could be explained by the limited vocabulary of Sino-Vietnamese related to economics of the students. Therefore, the paper concentrated on the appropriate strategies and procedures in order to translate economic terminology with Vietnamese Chinese-derived words in Vietnamese and proposed suggestions for the students to widen their knowledge of Sino-Vietnamese vocabulary. However, the study remained some limitations, which shed light on the further studies.